Periodismo deportivo por streaming y periodismo tradicional en Guayaquil - Parra Proaño, Rubén David (2021)
Guayaquil sports journalism has evolved, with the use of streaming some media have chosen to broadcast through these platforms. Sports radios in this city are divided into traditional and digital, radio stations continue to work in the same way as they have always done with the difference that now they have to use social networks as a way to be in contact with their audience , that there is an interactivity because this is something that online radios use as a strong point in their work methodology. Over the years, online radios have gained more strength in Guayaquil, they have begun to gain more popularity among people, because it is easier to make transmissions through a streaming platform through a computer, unlike a traditional radio where you need more equipment and other items. Due to this, a large part of people choose to work in this medium. In the methodological framework of the thesis, surveys were carried out with the audiences of radios such as La Radio Redonda, Sucre, Atalaya, América and Master Music, in turn journalists were interviewed one for each of these radios and elaborated observation cards choosing two traditional and two digital media. Taking as a qualitative-quantitative mixed approach. Giving as results that traditional radios are more tuned than online by Guayaquil, due to various factors such as the level of production, programming, the advertising aspect is also important because a large majority of digital ones are not well known In turn, radio station media have to invest more money, they must spend more equipment, computers, microphones, and workers' salaries, unlike streaming media, which do not have to invest as much in these aspects............